sin^(2)x=cosx+sinxcosx
in Trigonometry Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

sin^(2)x = cosx+sinxcosx

divide both sides by sin(x),

sin(x) = cot(x) + cos(x)

Imagine a right-angled triangle with

hypotenuse = 1+ t

opposite side = 2√t

adjacent side = 1 - t

We can now use the following substitutions for sin(x) cos(x) and cot(x).

sin(x) = 2√t/(1 + t)

cos(x) = (1 - t)/(1 + t)

cot(x) = (1 - t)/(2√t)

Making these substitutions into the final trig equation above,

2√t/(1 + t) = (1 - t)/(2√t) + (1 - t)/(1 + t)

Multiply both sides by (1 + t),

2√t = (1 – t2)/(2√t) + (1 - t)

Simplify by multiplying by 2√t, then multiplying out,

4t = 1 – t2 + 2√t – 2t3/2

Substituting for u^2 = t,

4u^2 = 1 – u^4 + 2u – 2u^3

u^4 + 2u^3 + 4u^2 - 2u – 1 = 0

Newton’s method of approximation

              x_(n+1) = x_n – f(x_n) / f‘(x_n)

We have f(u) = u^4 + 2u^3 + 4u^2 - 2u – 1

from which, f’(u) = 4u^3 + 6u^2 + 8u - 2

And

u_(n+1) = u_n – f(u_n) / f‘(u_n)

1st Approximation, u_0

The original equation is trigonometric. Solutions will (probably) be cyclic. A range from which to start would be [0, 2π].

A reasonable value for u_0, from which to start our iteration process, would be u_0 = 1.

 

n            u_n                     f(u_n)                 f’(u_n)                u_(n+1) = u_n – f(u_n) / f‘(u_n)

0            1                          4                          16                        0.75

1            0.75                     0.9101                 9.0625                 0.64957

2            0.64957              0.1148                6.8245                0.6327

3            0.6327                 2.93E-03             6.477                   0.63229

4            0.63229              2.09E-06             6.4683                 0.63229

5            0.63229

To 4 places of decimals, the solution is: u = 0.6323

Now, we have sin(x) = 2√t/(1 + t) = 2u/(1 + u^2), giving us

sin(x) = 2*0.6323 / (1 + 0.6323^2)

sin(x) = 1.2646 / 1.3998 = 0.9034

x = 1.1276 rad

by Level 11 User (81.5k points)

Related questions

1 answer
asked Mar 19, 2013 in Trigonometry Answers by anonymous | 2.0k views
1 answer
2 answers
1 answer
asked May 9, 2013 in Trigonometry Answers by anonymous | 1.7k views
0 answers
asked Jan 11, 2012 in Trigonometry Answers by anonymous | 603 views
1 answer
1 answer
asked May 24, 2013 in Calculus Answers by anonymous | 588 views
0 answers
asked Feb 5, 2013 in Calculus Answers by anonymous | 587 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
87,548 questions
99,681 answers
2,417 comments
465,624 users